El papel de las finanzas en la dinámica económica argentina entre 1976 y 2001 - BORDÓN, Marisa (Papeles de Europa, 2011)
Through certain economic policies undertaken by different governments from 1976 to 2001, the financial capital becomes the center of gravity through which the model of accumulation in Argentina articulates itself. This can be seen in the growth and the dynamism of the financial sphere not only in quantitative, but also in qualitative terms because it helps to explain the changes that occur in three dimensions: economic structure, social decline and external dependence. The behavior of State, nonfinancial and financial sector, the foreign capital and their interrelationships constitutes this new role of finance in economic dynamics.
Keywords: Model of accumulation; Financial capital; Economic dynamics; Economic policies